Everyone on this train is a suspect : a novel - Stevenson, Benjamin (New York, NY : Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
"I'm Ernest Cunningham. Call me Ern or Ernie. When the Australian Mystery Writers' Society invited me to their crime-writing festival aboard the Ghan, the famous train between Darwin and Adelaide, I was hoping for some inspiration for my second book. Fiction, this time: I needed a break from real people killing each other. But, the Ghan is not the respite I'd been hoping for. It turns out I've trapped myself on an 1,800-mile journey with a powder keg of grudges: crime writers with hidden secrets, overeager fans bearing conspiracy theories, and agents and editors undercutting each other in order to sign the next big thing. When one of us is murdered, the remaining writers turn into detectives. Together we should know how to solve a crime. Of course, we should also know how to commit one"--Provided by publisher.
Keywords: Cunningham, Ernest -- (Fictitious character) -- Fiction; Authors -- Fiction; Literature -- Societies, etc. -- Fiction; Fiction -- Authorship -- Fiction; Railroad travel -- Fiction; Murder -- Investigation -- Fiction; Railroad trains -- Australia -- Fiction; Detective and mystery fiction; Novels; Large print books